Design of Work Systems in Air Cooler Production Using Work Load Analysis (WLA) and Macroergonomic Analysis and Design (MEAD) Methods at PT GIJ - Fandra Prastyo Al Havish; Boy Isma Putra (Universitas Muhammadiyah Sidoarjo, 2022)
Air cooler is a system or machine designed to stabilize the air temperature and humidity in a certain area by circulating it. In the air cooler production process at PT GIJ, very high accuracy is also needed in the process and is still carried out by 1 worker in each part of the production process manually and the time it takes is relatively long up to more than 2 hours from normal time and results in employees fatigue easily. This study uses the work load analysis (WLA) method to reduce the workload obtained by completing the work at a certain working time and then improving the work system using the macroergonomic analysis and design (MEAD) method to determine the need for rest time in several production process activities. From the results of this study indicate the value of the workload after doing research using the work load analysis (WLA) method, the results of the workload at the component stage are 0.52 and the line process stage is 0.51 which means that from the stages of the production process each is declared to get a load. underload or normal work and the results obtained from the calculation of the need for rest time using the macroergonomic analysis and design (MEAD) method, the results of energy consumption are 2.52 kcal/minute and the results obtained are the need for rest time of 64.15 minutes so that the rest time needed by employees for stretching the body by 4.15 minutes outside the normal rest time of 60 minutes.